MENYUSUN RETURN POINT DAN TARGET PROFIT UNTUK BUSINESS PLAN (KAJIAN JAJANAN STIK BU MINARTI) - Hayati, Sari (Jurnal Manajemen, Akuntansi, Ekonomi, 2023)
The selling price is determined by the size of the cost, this aims to influence sales volume, but production volume is directly affected by sales, and costs are affected by sales volume where everything is interrelated with one another. The manager of the stick snack business is required to be able to make a decision to support the progress and goals set by the company. So that in the early stages of production this will determine the smooth running of the business so as not to suffer losses or at least return modale. This can show the success of a business from year to year whether it is progressing, fixed or declining. Return Points will be obtained when producing or selling 170 units of this product, and the total Renenue is IDR 17,000,000, then the target must be greater than 170 units, because if the target is below module 170 units, the company will incur a loss, if it is targeted to producing 230 units, the Total Revenue is IDR 23,000,000, the fixed costs are IDR 5,100,000, and the variable costs are IDR 16,100,000. The planned price/unit is IDR 100,000, so the company will modale return if it produces 170 units or sales IDR 17,000,000, and the company will get a profit of IDR 1,800,000 per month by selling 230 units of product in one month.